The Strategy Smart City Development Concepts in Indonesia - Hasna Anugerah Viola; Achmad Room Fitrianto (Jurnal Public Policy, 2022)
The government ability to manage the potencies and assets owned through digital technology is the key to developing a smart city. Standardization of public services procedur through ISO is the early stage in digitalizing the government services. This paper focuses on analyzing the implementation of the smart city concept in Indonesia and identifying the relevant, innovative strategies applied as a reflection of the transformation of urban areas. This paper aims to determine the effectiveness of digital public service facilities in improving the community's welfare. The paper employed a qualitative approach with a case study. The data gathered from journal articles, e-books, official government data and websites, the latest online news portals, and the data of relevant others agencies. The results show that the smart city concept development initiative in several cities and districts in Indonesia is increasing, in line with information and communication technology. Accordingly, the smart city strategy developed relies on ICT-in public services. Therefore, the processes require massive campaigns for the community to get used to it. In addition, having good communication and collaboration among all stakeholders in society creates a dynamic of sustainable urban development framed in smart city project design applied